2018
DOI: 10.3389/fpls.2018.01709
|View full text |Cite
|
Sign up to set email alerts
|

The Photorespiratory BOU Gene Mutation Alters Sulfur Assimilation and Its Crosstalk With Carbon and Nitrogen Metabolism in Arabidopsis thaliana

Abstract: This study was aimed at elucidating the significance of photorespiratory serine (Ser) production for cysteine (Cys) biosynthesis. For this purpose, sulfur (S) metabolism and its crosstalk with nitrogen (N) and carbon (C) metabolism were analyzed in wildtype Arabidopsis and its photorespiratory bou-2 mutant with impaired glycine decarboxylase (GDC) activity. Foliar glycine and Ser contents were enhanced in the mutant at day and night. The high Ser levels in the mutant cannot be explained by transcript abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…However, knock-down of the PSP gene did not affect Ser contents in either mutant line, indicating that Ser synthesis was not regulated by transcriptional changes of genes of the photorespiratory pathway under the conditions applied. Both psp mutant lines showed a reduced transcript amount of key genes of nitrogen assimilation, also observed in the bou-2 mutant, grown at elevated and shifted to ambient CO 2 (Samuilov et al, 2018). In addition, similar to the bou-2 mutant, an enhanced GABA pool size and GAD1 transcript amount was observed at day and night for both psp mutant lines (Figure 4).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, knock-down of the PSP gene did not affect Ser contents in either mutant line, indicating that Ser synthesis was not regulated by transcriptional changes of genes of the photorespiratory pathway under the conditions applied. Both psp mutant lines showed a reduced transcript amount of key genes of nitrogen assimilation, also observed in the bou-2 mutant, grown at elevated and shifted to ambient CO 2 (Samuilov et al, 2018). In addition, similar to the bou-2 mutant, an enhanced GABA pool size and GAD1 transcript amount was observed at day and night for both psp mutant lines (Figure 4).…”
Section: Discussionmentioning
confidence: 71%
“…The processes involved in these metabolic changes require further attention. The shift from elevated to ambient CO 2 resulted in an accumulation of amino acids such as Ala, Ile, Leu and Thr in the bou-2 mutant (Eisenhut et al, 2013; Samuilov et al, 2018). Under the same growth conditions, also both psp mutant lines showed increased amounts of these amino acids at day and night (Supplementary Figure S4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst we have made great advances in our understanding as to how the photorespiratory pathway evolved and how it is currently fully embedded within the primary metabolism of plants and algae, new research avenues in understanding the native pathway still exist (Box 2). Prominent recent examples include the interaction of photorespiration with S metabolism maybe by providing serine for O ‐acetylserine and hence cysteine formation (Samuilov et al , ), and the intriguing suggestion that metal ion availability could regulate photorespiration (Bloom and Lancaster, ). Thus, considerable research is needed in order to complete our understanding of this fascinatingly complex pathway.…”
Section: Discussionmentioning
confidence: 99%
“…O ‐acetylserine is required for cysteine and glutathione metabolism. Indeed, it was shown that the bou mutant displays reduced serine concentrations and shows altered transcription in S metabolism associated genes (Samuilov et al ., ).…”
Section: The Core Photorespiratory Pathway and Its Metabolic Interdepmentioning
confidence: 97%